-7x-3=85+x

Simple and best practice solution for -7x-3=85+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x-3=85+x equation:


Simplifying
-7x + -3 = 85 + x

Reorder the terms:
-3 + -7x = 85 + x

Solving
-3 + -7x = 85 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + -7x + -1x = 85 + x + -1x

Combine like terms: -7x + -1x = -8x
-3 + -8x = 85 + x + -1x

Combine like terms: x + -1x = 0
-3 + -8x = 85 + 0
-3 + -8x = 85

Add '3' to each side of the equation.
-3 + 3 + -8x = 85 + 3

Combine like terms: -3 + 3 = 0
0 + -8x = 85 + 3
-8x = 85 + 3

Combine like terms: 85 + 3 = 88
-8x = 88

Divide each side by '-8'.
x = -11

Simplifying
x = -11

See similar equations:

| 2g+12=22-10g | | 6-tanx=2sec^2x | | x+34=2x+12 | | 3m+13=42-9m | | 3m+13=42-9 | | z^2-26z+169=0 | | 7-3x+6x=40 | | 4+m=-1 | | 2x^3+5x^2-98x+245=0 | | x^2+9x-2=5 | | 4t-3/5-4-2t/3=1 | | -9n+(-2)+3x-n+4= | | 5+4=n | | S^2-145+45=0 | | 5+9s-3=6s+23-4s | | 2x(x-3)+5(x-3)=0 | | 19-n=n-5 | | x=2+3+20-30+60-190+25-30+21 | | 25(e+6.25)=443.75 | | 1x=3x+70 | | X-7-3x=-21 | | 10(e+5)=280 | | Y/-3=1/6 | | x(x-10)=-34 | | -2(x-3)=2-(x+3) | | 3d^2+5d-6=0 | | -16=x+23 | | 5x=9-3 | | -5-2x=3-6 | | 21x+30=20-3 | | x-6=.66666666666666y | | -5x+6=-9x+22 |

Equations solver categories